RESISTENSI GURU MENGAJAR DI DAERAH TERPENCIL - Muhaimin, Muhaimin; Kristiawan, Muhammad (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
These studies emphasize the motivation of teachers to survive teaching in remote areas and their roles, with a focus on research into factors that can make teachers survive teaching. The purpose of this study was to determine the motivation of teachers to survive teaching in remote areas and its role in Elementary School 23 Pulau Rimau Purwodadi Village P.13 KAT Pulau Rimau District Banyuasin District with the main data sources were 4 teachers as informants. This research is qualitative, with a case study approach. While the technique of collecting data through interviews, observation, and documentation studies. The data analysis technique in this study is through drawing conclusions. The results of this study are the motivational factors of the surviving teacher, namely; (1) a sense of responsibility for the education of children in remote areas; (2) the teacher enjoys work as a noble proposition; (3) the teacher receives good appreciation from the local community; (4) a conducive environment; (5) moral encouragement from the principal. By knowing and being aware of the role as educators, teachers at 23 Pulau Rimau Elementary Schools can sincerely serve and carry out their duties well.